Some aspects of the economic philosophy of the World Bank : transcription of talks by World Bank economists at a Seminar for Brazilian professors of Economics in Rio de Janeiro, 18 - 22 September 1967, and since brought up to date (Rio de janeiro : International Bank for Reconstruction and Development, 1968)
The book deal with some details aspects of the economic philosophy of the World Bank
msa 03/01/2018
Loans
Keywords: World Bank